O ensino de línguas estrangeiras no Brasil: um processo excludente - Quadrado, Alessandro França (2014)
The academic discipline of Foreign Languages is embedded in the curriculum of Brazilian schools by law. However, its inclusion does not guarantee its teaching process to be effective. Given this, private language courses have bridged the gap left by the school. From this perspective, the teaching and learning of foreign languages is limited to a number of students that study them according to an instrumental bias in these courses, which provide the learning of language skills, but that usually don’t bring critical thinking necessary for an emancipatory education. Against this background, this article aims to contextualize foreign language teaching in Brazil starting with its brief history and current situation. Furthermore, the relevance of this discipline in the context of basic education is discussed as something essential. Finally are listed some conditioning factors that can help to reverse the exclusionary process of foreign language teaching in Brazil.